Orientation Dependence of Compression Deformation on 1570C Aluminum Alloy; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Chumaevskii A. V.; Tarasov S. Yu. Sergei Yulievich; Kalashnikova T. A.; Kolubaev Е. А. Evgeny Aleksandrovich (2016, 2016)
Title screen